2017
DOI: 10.1051/0004-6361/201630158
|View full text |Cite
|
Sign up to set email alerts
|

A star formation study of the ATLAS3Dearly-type galaxies with the AKARI all-sky survey

Abstract: Context. The star formation properties of early-type galaxies (ETGs) are currently the subject of considerable interest, particularly whether they differ from those of gas-rich spirals. Aims. We perform a systematic study of star formation in a large sample of local ETGs using polycyclic aromatic hydrocarbon (PAH) and dust emission, focusing on the galaxies' star formation rates (SFRs) and star formation efficiencies (SFEs). Methods. Our sample is composed of the 260 ETGs from the ATLAS 3D survey, from which w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 96 publications
(122 reference statements)
3
46
1
Order By: Relevance
“…of PGC 26218. Kokusho et al (2017) studied the star formation of the same sample as Davis et al (2014) in ATLAS 3D survey. They found that the local ETGs have the similar star formation efficiency to the star-forming galaxies and follow the K-S law.…”
Section: Sfms and K-s Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…of PGC 26218. Kokusho et al (2017) studied the star formation of the same sample as Davis et al (2014) in ATLAS 3D survey. They found that the local ETGs have the similar star formation efficiency to the star-forming galaxies and follow the K-S law.…”
Section: Sfms and K-s Lawmentioning
confidence: 99%
“…The difference between them might be attributed to the methods of calculating SFR. Davis et al (2014) calculated the SFR via FUV and 22 µm, while Kokusho et al (2017) via the spectral energy distributions fitting. Colombo et al (2018) combined the CO observations made by the Combined Array for Millimeter-wave Astronomy from Extragalactic Database for Galaxy Evolution survey (Bolatto et al 2017) with the 2D-spectroscopic observations made by CAHA from Calar Alto Legacy Integral Field Area survey (Sánchez et al 2012).…”
Section: Sfms and K-s Lawmentioning
confidence: 99%
“…Using the AKARI all-sky maps (Murakami et al 2007;Doi et al 2015;Ishihara et al, in prep. ), Kokusho et al (2017) systematically measured the 9, 18, 65, 90, and 140 µm band fluxes of the ATLAS 3D ETGs. They performed aperture photometry within a circular aperture of radius R aper = (2R e ) 2 + (1.5D PSF ) 2 , where R e and D PSF are respectively the effective radius of the galaxy in the optical B band (Cappellari et al 2011a) and the full width at half maximum of the AKARI point spread function (PSF) in the relevant band (Ishihara et al 2010;Takita et al 2015).…”
Section: Akari All-sky Surveymentioning
confidence: 99%
“…They performed aperture photometry within a circular aperture of radius R aper = (2R e ) 2 + (1.5D PSF ) 2 , where R e and D PSF are respectively the effective radius of the galaxy in the optical B band (Cappellari et al 2011a) and the full width at half maximum of the AKARI point spread function (PSF) in the relevant band (Ishihara et al 2010;Takita et al 2015). Combining the AKARI measurements with Wide-field Infrared Survey Explorer (WISE; Cutri et al 2013) and Two Micron All Sky Survey (2MASS; Skrutskie et al 2006;Griffith et al 2015) data, Kokusho et al (2017) decomposed the resulting spectral energy distributions (SEDs) into polycyclic aromatic hydrocarbon (PAH), warm dust, and cold dust emission. For the dust emission, Kokusho et al (2017) used a two-temperature modified blackbody model with fixed emissivity power-law index β = 2.…”
Section: Akari All-sky Surveymentioning
confidence: 99%
See 1 more Smart Citation